2021
DOI: 10.1186/s12909-020-02464-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of medical students towards the practice of professionalism at the Arabian Gulf University

Abstract: Background To enhance the development of a curriculum in professionalism for medical students, the aim of this research was to evaluate medical students’ responses regarding professionalism teaching and behaviors in their clinical experience at the Arabian Gulf University (AGU). Methods A retrospective cross-sectional, questionnaire-based study involving Year 5 medical students at the AGU. We used a “climate of professionalism” survey that consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
3
9
0
2
Order By: Relevance
“…It is interesting that another study has reported that both students and residents consider their own group more professional than the other group simultaneously ( 33 ). Al Gahtani et al, who used the same instrument as we did, found that students rated their peers’ professional behavior higher than that of faculty and residents ( 36 ). The explanation may be that residents usually spend more time in the hospital than students and faculty members and are exposed to more workload and stress, and so their threshold for unprofessional behaviors lowers.…”
Section: Discussionsupporting
confidence: 54%
“…It is interesting that another study has reported that both students and residents consider their own group more professional than the other group simultaneously ( 33 ). Al Gahtani et al, who used the same instrument as we did, found that students rated their peers’ professional behavior higher than that of faculty and residents ( 36 ). The explanation may be that residents usually spend more time in the hospital than students and faculty members and are exposed to more workload and stress, and so their threshold for unprofessional behaviors lowers.…”
Section: Discussionsupporting
confidence: 54%
“…is a culture-sensitive concept and any tool for measuring its constructs in the clinical setting should reflect the cultural context (14).…”
Section: History Of Medicinementioning
confidence: 99%
“…In addition, the development and application of questionnaires at the beginning of professionalism enhancement programs could encourage the involved people (residents, faculty members and staff) to adhere to professional codes and improve the current situation ( 12 , 13 ). Professionalism is a culture-sensitive concept and any tool for measuring its constructs in the clinical setting should reflect the cultural context ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients need to be able to trust their caregivers with their health and life. 6 One of the most effective strategies to combat academic dishonesty is creating policies and codes of honour to nurture a culture of academic integrity. 7 It has been shown that students who engage in cheating behaviours have little knowledge of these policies.…”
Section: Introductionmentioning
confidence: 99%
“… 5 This is particularly troublesome among healthcare professionals who are expected to be sincere and trustworthy given that patients need to be able to trust their caregivers with their health and life. 6 …”
mentioning
confidence: 99%